O sistema modular de ensino em Abaetetuba: trajetórias de implantação e afirmação do SOME no rio Piquiarana-Açú - SILVA, Gevanildo dos Santos (2025)
The study discusses the implementation and affirmation trajectories of SOME in the municipality of Abaetetuba, particularly in the community of PiquiaranaAçu. SOME emerges as a teaching project aimed at making up for the absence of 2nd grade education in several locations in the interior of the extensive state of Pará, and offering the opportunity to complete basic education in a place close to your home. The main objective is to understand the importance of SOME for riverside localities, as well as its main difficulties in the provision of education, focusing on the locality of the Piquiarana-Açú River. To this end, a qualitative approach was used, and bibliographic research was carried out. To this end, we studied authors who have already discussed and evaluated the theme from a historical and relevant point of view, in addition to using some legislation. A description of the facts that make up the historical trajectory of SOME in Pará, then in Abaetetuba and then in the Community of the Piquiarana-Açú River was carried out. After that, a discussion was established about the relevance and the difficulties and limitations presented in the execution of the Project. It is concluded that the Modular Teaching Organization System — SOME; emerged as an innovative strategy with the purpose of making up for the lack of high school in Pará and beyond this, the Higher Elementary School, in Abaetetuba and in other interior regions of the state. And that, despite the difficulties and instabilities found in the project, is of paramount importance for the localities served by it.